Palm-tocotrienol rich fraction has hypohomocysteinemic effect in rats fed high methionine diet - Ku Zaifah, Norsidah; Yusuf, Kamisah; Yusuf, Ahmad Asmadi; Ayob, Azizi (2011)

(untitled)
Hyperhomocysteinemia is associated with increased risk of cardiovascular disease (1). It is associated with elevation of oxidative stress (2). The aim of this study was to determine the effects of palm-tocotrienol rich fraction (TRF), a known anti-oxidant, at various doses on plasma total homocysteine level (tHcy) and activity of hepatic cystathionine-β-synthase (CBS) in rats fed high methionine diet, as compared to folate. Forty-two male Wistar rats were divided into six groups. Group 1 was the control. Groups 2 to 6 were fed 1% methionine diet for 10 weeks. From week 6 onward, folate (8 mg/kg diet) or palm TRF (30, 60 or 150 mg/kg diet) were added into the diet of groups 3, 4, 5 and 6. Body weights were recorded weekly. The rats were then sacrificed and plasma tHcy at week 0, 5 and 10, and the activity of liver cystathionine-β-synthase were determined. Statistical Package for Social Sciences (SPSS) 11.5 was used. Data is presented as Mean ± SEM. P < 0.05 is considered significant. High methionine diet did not affect body weight. It raised plasma total homocysteine (tHcy) but was prevented by palm TRF at various doses, as well as folate. However, unlike folate, palm TRF significantly caused reduction of liver CBS activity.